Flavonoid glycosides from leaves and straw of Oryza sativa and their effects of cytotoxicity on a macrophage cell line and allelopathic on weed germination - Ill-Min Chung; Sung-Kyu Park; Mohd Ali; Mayakrishnan Prabakaran; Young-Tek Oh; Seung-Hyun Kim; Nasir Ali Siddiqui; Ateeque Ahmad (Elsevier, 2018)
Five new flavonoids namely, 5-hydroxy-6-isoprenyl-7,4'-dimethoxyflavonol-3-O-β-d-arabinofuranoside (1), 5,7-dihydroxy-4'-methoxyflavone-7-O-β-d-arabinopyranosyl-2''-n-decan-1'''-oate (2), 3-butanoyl-5,6,8-trihydroxy-7,4'-dimethoxyflavonol--5-O-β-d-glucopyranoside (3), 7, 4'-dimethoxy-5-hydroxyflavone-5-O-α-d-arabinopyranosyl-(2'' → 1''')-O-α-d-arabinopyranoside (4), and 5,6-dihydroxy-7, 4'-dimethoxyflavone-5-O-α-d-glucopyranoside (5), together with two known compounds, were isolated from the methanol extract of Oryza sativa leaves and straw. Their structures of new compounds were elucidated by 1D and 2D NMR spectral methods, viz: COSY, HMBC and HSQC aided by mass techniques and IR spectroscopy. The cytotoxicity of these compounds (1-7) were assessed by using (RAW 264.7) mouse macrophages cell line, and allelopathic effects of compounds (1-7) on the germination characteristics of barnyardgrass (Echinochloa oryzicola) and pigweed (Chenopodium album L.) were also evaluated. The compounds 1, 6 and 7 showed cytotoxicity and compounds 1-7 exhibited significant inhibitory activity on the seed germination of two weed species.